CONTENTS OF MUSIC LESSONS AND REQUIREMENTS FOR ORGANIZATION - Umarova A. I. (American Journals, 2022)
The goals and objectives of the "Music culture" lesson in general education schools, teaching methods, requirements set by the state educational standard, ways of organizing lessons based on new pedagogical technologies, and lesson development by classes samples are provided.
Keywords: music, lesson, music literacy, rhythmic and musical movements, technology